Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/0284186x.2014.969846
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-induced neuropathy: A pharmacogenetic case-control study of 150 women with early-stage breast cancer

Abstract: We found that GSTP1 Ala114Val polymorphism is associated with occurrence of DIPN. This supports the theory that oxidative stress is involved in DIPN pathophysiology. If confirmed, this may be helpful in the risk assessment of DIPN and perhaps help to achieve better management of neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 25 publications
2
53
1
Order By: Relevance
“…Consistent with previous reports in patients with colon cancer who received oxaliplatin 96 and patients with breast cancer who received docetaxel, 97 as well as patients with fibromyalgia 98 and diabetes mellitus, 99 patients with CIN had a higher BMI. As expected, and consistent with recent studies, 78,100 patients with CIN were more likely to have received a combination of a platinum and a taxane compound and had received higher cumulative doses of CTX.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous reports in patients with colon cancer who received oxaliplatin 96 and patients with breast cancer who received docetaxel, 97 as well as patients with fibromyalgia 98 and diabetes mellitus, 99 patients with CIN had a higher BMI. As expected, and consistent with recent studies, 78,100 patients with CIN were more likely to have received a combination of a platinum and a taxane compound and had received higher cumulative doses of CTX.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, heterogeneity between the patient cohorts, including differences in gender, age, and functional status, or differences in the phenotype (grade 2+ vs. grade 3+), may explain the lack of replication across the clinical GWAS. This GWAS was also not able to replicate previously reported associations between docetaxel-induced neuropathy and SNPs in ABCB1 (15) or GSTP1 (13, 14) reported in previous candidate SNP studies, similar to the failure of paclitaxel GWAS to replicate associations with candidate SNPs including CYP2C8*3 (32). …”
Section: Discussioncontrasting
confidence: 77%
“…[41][42][43] In that literature, marital satisfaction, spousal support, and spousal responses to pain reportedly can contribute to psychological distress (depressive symptoms, anxiety symptoms, and mood disorders) which, in turn, is associated with pain dimensions, including symptom severity. 4,11,39,40,44 In the current study, a history of vigorous exercise prior to chemotherapy was not identified as a factor in the development of CIPN, although other studies have shown significantly reduced CIPN in women who were physically active prior to receiving chemotherapy. In our multivariable model, these quality-of-life measures were collected before, not after, neurotoxic chemotherapy was received.…”
Section: Discussionmentioning
confidence: 49%